Puffing/micro-explosion in composite fuel/water droplets heated in flames; Combustion and Flame; Vol. 233 - Antonov D. V. Dmitry Vladimirovich; Fedorenko R. M. Roman Mikhaylovich; Strizhak P. A. Pavel Alexandrovich; Nissar Z. Zuhaib; Sazhin S. S. Sergey Stepanovich (2021, 2021)
Title screen